Pembelajaran Berbasis Proyek Menggunakan Software Matematika Geogebra Terhadap Kemampuan Komputasi Siswa - Nur Aisyah Hasibuan; Yahfizam Yahfizam (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The use of digital technology in mathematics education material makes it a very interesting and urgent matter regarding the level of students' abilities regarding the material they are studying, whether students understand mathematics material more easily or have more difficulty understanding it. Geogebra is a free math learning software program that supports a variety of math topics. for use at school. Initially, GeoGebra was only used for learning algebra and geometry, but as it developed, many new features were added and increasingly enriched the existing features. The research method used in this research uses a literature study research method where researchers study the results of previous research. The results of this research conclude that the use of Geogebra mathematics software in learning has a positive influence on students' computing knowledge, learning through Geogebra software makes mathematics learning easier for students to understand and understand, students are more enthusiastic about studying mathematics because teachers balance conventional and mathematics. integrated mathematics learning. Project-based learning using Geogebra mathematics software is more popular with students, thereby increasing students' abilities and enthusiasm for learning mathematics.